Survival and Growth of Listeria monocytogenes in Refrigerated Fish - G., Jeyasekaran; I., Karunasagar; I., Karunasagar (Fishery Technology, 2025)
The ability of Listeria monocytogenes to survive and grow in fish at refrigerated condition was studied. Fresh, white sardine (Kowala coval) were washed and inoculated with L monocytogenes (NCTC 1994) at a level of 104 cfu.g"1. The inoculated fish were kept at room temperature (28Â±20C) for 6 h and then stored at refrigerated condition (4Â±10C). The fish was found to have a load of 105 cfu.g"1 of L. monocytogenes after the temperature abuse. Though there was a minimal increase in the count during the first two days of refrigerated storage, a slight reduction in counts was observed on the 4th day of chilled storage and thereafter the counts did not show appreciable change. The results suggest that chilling does not have a significant effect on the control of L. monocytogenes in fish and there is a possibility of contaminated seafood acting as a vehicle of infection.